Study on diversity of the CCT-delta gene from soybean cultivars - Phuong Lien, Tran Thi; Thu Hien, Le Thi; Ton, Nguyen Dang; Hieu, Cao Xuan; Hai, Nong Van; Muoi, Le Thi; Long, Tran Dinh (Academia Journal of Biology, 2015)
Study on diversity of the CCT-delta gene from soybean cultivars